1999
DOI: 10.1080/014850199262995
|View full text |Cite
|
Sign up to set email alerts
|

Male Fertility of Kidney Transplant Patients With One to Ten Years of Evolution Using a Conventional Immunosuppressive Regimen

Abstract: The reproductive functions and hormone serum levels of 55 male kidney transplant recipients were assessed. Patients underwent peritoneal dialysis before transplantation and were given immunosuppressive therapy afterward for 1 to 10 years. Spermatobioscopies were performed, and serum urea, creatinine, luteinizing hormone (LH), follicle-stimulating hormone (FSH), prolactin (PRL), and testosterone (T) levels were determined. Average serum urea and creatinine levels were 54.6+/-1.4 and 3+/-1.3 mg/dL, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 14 publications
2
37
0
Order By: Relevance
“…In these patients, the semen analysis typically showed a decreased volume of ejaculate, oligo-or complete azoospermia and a low percentage of motile sperms. Besides, the presence of orchiatrophy in the advanced stage of uremia has been also reported [12]. The spermatobioscopy results revealed that azoospermia and oligozoospermia were present in 50% of the patients.…”
Section: Discussionmentioning
confidence: 89%
“…In these patients, the semen analysis typically showed a decreased volume of ejaculate, oligo-or complete azoospermia and a low percentage of motile sperms. Besides, the presence of orchiatrophy in the advanced stage of uremia has been also reported [12]. The spermatobioscopy results revealed that azoospermia and oligozoospermia were present in 50% of the patients.…”
Section: Discussionmentioning
confidence: 89%
“…The normalization of LH and a tendency towards increasing testosterone levels after kidney transplantation suggests that Leydig cell impairment is rapidly resolved by kidney transplantation. However, sperm quality measured as sperm count, motility, and morphology does not seem to improve as fast as hormone levels [6, 15, 16]. Indeed, there are reports of continuously improved sperm quality during 2 years after transplantation and reports of transplanted men not regaining the sperm motility function [17].…”
Section: Discussionmentioning
confidence: 99%
“…The sex hormone profile tends to normalize; plasma testosterone and follicle stimulating hormone levels increase; and luteinizing hormone levels which may be high in dialysis patients, decrease to normal or low levels (Danovitch GM 2005). The factors that might cause certain difficulties for the recovery of sexual and reproductive functions in this type of patients include prolonged use of peritoneal dialysis, high follicle stimulating hormone (FSH) serum levels before the transplant, and a deficient function of the graft (De Celis and Pedron-Nuevo 1999). A certain improvement has been reported as to semen quality in the three main parameters (number, morphology, and motility of the spermatozoa) in patients after kidney transplantation (De Celis and Pedron-Nuevo 1999).…”
Section: Renal Transplantationmentioning
confidence: 99%
“…The factors that might cause certain difficulties for the recovery of sexual and reproductive functions in this type of patients include prolonged use of peritoneal dialysis, high follicle stimulating hormone (FSH) serum levels before the transplant, and a deficient function of the graft (De Celis and Pedron-Nuevo 1999). A certain improvement has been reported as to semen quality in the three main parameters (number, morphology, and motility of the spermatozoa) in patients after kidney transplantation (De Celis and Pedron-Nuevo 1999). Several studies conducted to evaluate the effects of immunosuppressive regimens suggest that some of these agents are potentially gonadotoxic since they affect testicular function and decrease fertility.…”
Section: Renal Transplantationmentioning
confidence: 99%